Rémy Chauvin (1913–2009) - Evrard, Renaud (Journal of Scientific Exploration, 2010)
Rémy (André Joseph) Chauvin was a French biologist and entomologist, Professor Emeritus at the University Paris V-Sorbonne. His brilliant scientific career led him to successively direct three laboratories: the Laboratory of biology of the bee at the National Institute of Agronomic Research (INRA) in Bures-sur-Yvette, from 1948 to 1964; the laboratory of psycho-physiology in Strasbourg, from 1964 to 1968; and the Experimental ethnology laboratory of the École Pratique des Hautes Études (University of Paris, Mittainville), from 1969 on. He was an authority on the science of social insects and birds. Tributes from his colleagues praise his enthusiasm, his openness, and his dynamism, qualities that made him an exceptional research director (Arnold, 2010). Author of more than 50 books (with translations in 11 languages including Japanese), he wrote on topics ranging from the academic textbook to the science fiction novel, to the popularization of science, sociology of science, and philosophical essays. Chauvin wrote at least 200 scientific publications and supervised Ph.D. candidates for more than 35 years. JSE's readers probably know that Rémy Chauvin was an early Council member of the SSE. "Scientific exploration" truly expresses the process that motivated his research in frontier areas. I will describe his important role in the development of parapsychology in France and his other adventures into unorthodox areas.